2008
DOI: 10.1111/j.1750-3841.2008.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whey Protein Coating on Quality Attributes of Low‐Fat, Aerobically Packaged Sausage during Refrigerated Storage

Abstract: Whey protein-based edible coating was used to reduce oxidative degradation and microbial growth of low-fat sausages (LFSs) stored at 4 degrees C for 8 wk, under aerobic package. Whey protein coating reduced (P<0.05) thiobarbituric acid-reactive substances (TBARS) and peroxide value (PV) formation compared to control sausages. The percent inhibition of TBARS and PV for whey protein-coated sausages, compared to the control, was 31.3% and 27.1%, respectively. The ability of the whey protein coating to provide a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…During the preparation of the coating solution, the mixture was heated at 90C for 30 min, producing disulfide bonds and greater surface hydrophobicity (Shon and Haque 2007c). Previous reports show that edible protein films containing calcium salts have the potential to decrease water vapor permeability in vegetables and fruit (Shon and Haque 2007a) and low-fat sausage (Shon and Chin 2008). Because protein-based compounds are immiscible, they have to be emulsified in the coating to be effective.…”
Section: Percent Moisture Loss (Pml)mentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of the coating solution, the mixture was heated at 90C for 30 min, producing disulfide bonds and greater surface hydrophobicity (Shon and Haque 2007c). Previous reports show that edible protein films containing calcium salts have the potential to decrease water vapor permeability in vegetables and fruit (Shon and Haque 2007a) and low-fat sausage (Shon and Chin 2008). Because protein-based compounds are immiscible, they have to be emulsified in the coating to be effective.…”
Section: Percent Moisture Loss (Pml)mentioning
confidence: 99%
“…Edible films and coatings preserve fresh and frozen meat products and have been summarized in a previous review article ( Krochta and De Mulder-Johnston 1997). In recent years, edible films or coatings included casein, collagen, chitosan, gelatin, soy protein, whey protein, calcium alginate and methyl cellulose-based films (Were et al 1999;Shon and Haque 2007a;Shon and Chin 2008). These edible films or coatings can also be used as carriers for antimicrobials and antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the good moisture-barrier properties of gelatin coating. Previous reports demonstrated that whey protein coating reduced the moisture loss in cut LFSs (Shon and Chin, 2008) and cut beef steak (Haque et al, 2009). During the preparation of the coating solution, the mixture is heated at 90 o C for 30 min, producing disulfide bonds and greater surface hydrophobicity (Shon and Haque, 2007).…”
Section: Percent Moisture Loss (Pml)mentioning
confidence: 99%
“…The LFSs were manufactured as described by Shon and Chin (2008). Fresh pork hams, from pigs which had been slaughtered a day earlier, were purchased from a local retail meat market, and all visible fats and connective tissues were removed.…”
Section: Manufacture Of Low-fat Sausages (Lfss)mentioning
confidence: 99%
“…Ten years later Le Tien et al [20] showed that milk protein coatings are able to counteract oxidative degradation of cut fruits and vegetables through polyphenol oxidase inhibition. From then several polysaccharides (chitosan, alginate, methylcellulose or pectin) and proteins (casein, collagen, gelatin, phaseolin, zein, soy or whey proteins), or mixtures of them, were shown to give rise to edible films effective as water vapor and gas barriers for a wide range of food products and as carriers for antimicrobials [17,[21][22][23][24][25]. In particular, antimicrobial containing films are recently gaining potential interest in reducing the deleterious effects caused by also minimal cut processing of fresh fruits and vegetables [26,27].…”
mentioning
confidence: 99%